Relationships between load, wellness and injury in elite junior Australian football: It may not be the load but how well you cope that matters - Gastin, P. (27th Annual Congress of the European College of Sport Science (ECSS), Sevilla, 30. Aug - 2. Sep 2022, 2022)
INTRODUCTION: Elite junior Australian football players experience high loads across levels of competition and training [1]. High loads have been linked to the risk of injury, either in a linear or curvilinear (U-or J-curve) fashion [2]. Few studies have adjusted for variables that may influence the load-injury relationship such as how well players respond or cope with the physical and mental stresses of their sport [3]. The purpose of this study was to investigate the relationships between player load, wellness and injury. We hypothesised that player wellness would mediate and/or moderate the load-injury relationship.